Dermatovenerology: textbook for students of medical higher educational institutions with a specialization in the disciplines 060101 "Medical care" and 060103 "Pediatrics" in the discipline "Dermatovenerology" - Чеботарев, В. В. дерматовенерология 19400228 Вячеслав Владимирович (Textbook, 2020)
This course book discloses a current state of all the main sections of dermatic and sexuallytransmitted diseases, as provided by the standard curriculum for students of medical higher educationalinstitutions with a specialization in the disciplines 060101 "Medical care" and 060103 "Pediatrics" in thediscipline "Dermatovenerology". The primary focus is devoted to the clinical picture of dermatic and sexually transmitted diseases in adults and children, their etiology, pathogenesis, modern methods of treatment and prophylactics.The course book is illustrated with color photos of patients from the resources of the subdepartment. It represents tasks to each chapter, crosswords, which summarize the materials of the chapters. This edition is aimed not only at reading the material but its reasoning, solving situational tasks, which contributes to the development of the clinical thinking. The course book is dedicated for training the students of medical higher educational institutions of general medicine and pediatrics departments.